PERAN WISATA RELIGI BERENDO DALAM PEMBERDAYAAN EKONOMI LOKAL KOTA BENGKULU - Serviani, Serviani; Sintia Rahayu,; Nonie Afrianty, (JEMBA: JURNAL EKONOMI, MANAJEMEN, BISNIS DAN AKUNTANSI, 2024)
Berendo religious tourism in Bengkulu City has great potential to empower the local economy through cultural and religious-based tourism activities. This research aims to examine how Berendo religious tourism contributes to increasing local community income, creating job opportunities, and encouraging the growth of micro, small and medium enterprises (MSMEs) around the destination. The research method uses a descriptive approach with data collection techniques through interviews, observation and documentation. The research results show that Berendo religious tourism has a significant impact on local economic empowerment through increasing community income, providing employment opportunities, and increasing MSME income. It is recommended that local governments continue to support the development of religious tourism through policies that support local communities and MSMEs